Chemotherapy- and Immune-Related Gene Panel in Prognosis Prediction and Immune Microenvironment of SCLC - Chen, Meng-Yu; Zeng, Yue-Can; Zhao, Xi-He (Frontiers in Cell and Developmental Biology, 2022)
Small-cell lung cancer (SCLC) is a highly proliferative, invasive lung cancer with poor prognosis. Chemotherapy is still the standard first-line treatment for SCLC, but many patients relapse due to chemoresistance. Along with advances in immunology, it is essential to investigate potential indicators of the immune response and the prognosis of SCLC. Using bioinformatics analysis, we identified 313 differentially expressed genes (DEGs) in SCLC and normal lung samples, and we found that four upregulated genes (TOP2A, CDKN2A, BIRC5, and MSH2) were associated with platinum resistance, while immune-related genes (HLA family genes) were downregulated in SCLC. Then, a prognostic prediction model was constructed for SCLC based on those genes. Immune cell infiltration analysis showed that antigen presentation was weak in SCLC, and TOP2A expression was negatively correlated with CD8+ T cells, while HLA-ABC expression was positively correlated with M1 macrophages, memory B cells, and CD8+ T cells. We also found that TOP2A was related to poor prognosis and inversely correlated with HLA-ABC, which was verified with immunohistochemical staining in 151 SCLC specimens. Our study findings indicated that TOP2A may be a potential prognosis indicator and a target to reverse the immunosuppressive tumor microenvironment of SCLC.